Neuroprotection by rAAV-mediated gene transfer of bone morphogenic protein 7 - Heinonen, Ann-Marie; Rahman, Mahbubur; Dogbevia, Godwin; Jakobi, Hannah; Wölfl, Stefan; Sprengel, Rolf; Schwaninger, Markus (BMC neuroscience, 2014)
Bone morphogenic proteins (BMPs) promote the survival of neurons, suggesting a therapeutic application of BMPs in the treatment of acute and chronic neurodegenerative disorders. However, the application of recombinant BMPs in vivo is limited by their short half-life. To provide a continuous supply for functionally active BMPs, we expressed BMP7, BMP2 and the BMP inhibitor Noggin under the control of rAAV vectors in vivo. For visual control of rAAV-mediated BMP (v-BMP) expression we fused the secreted morphogenic polypeptides and the fluorescent reporter protein Venus via the ‘ribosomal skip’ promoting 2A peptide-bridge.
Gesehen am 22.09.2020